Long-term improvement of dyslipidaemia, hyperuricemia and metabolic syndrome in patients undergoing laparoscopic sleeve gastrectomy - Cornelia Zetu; Simona Popa; Andreea-Loredana Golli; Ancuta Condurache; Rubin Munteanu (Archives of Endocrinology and Metabolism, 2020)
ABSTRACT Objective The aim of the study was to assess the long-term impact of laparoscopic sleeve gastrectomy (LSG) on lipid profile, uric acid level and metabolic syndrome. Materials and methods A prospective study was performed between 2009-2014, evaluating long-term percentage of excesso body mass index loss (%EBMIL), lipid profile, uric acid level and metabolic syndrome. Results Overall sixty subjects were followed-up. %EBMIL increased significantly, reaching a maximum (86,9 ± 6,3%) at 5 years post-LSG. Therapeutic success rate (%EBMIL ≥ 60%) was 80% at 5 years. The triglyceride level decreased significantly (148 ± 72.1 mg/dL baseline vs 130.7 ± 57.5 mg/dL at 1 month vs 110.7 ± 42.6 mg/dL at 3 months vs 92.5 ± 35.2 mg/dL at 1 year vs 84.2 ± 32.3 mg/dL at 5 years; p < 0.05 for all). HDL-cholesterol increased and uric acid decreased significantly in the first year postoperatively, remaining stable afterwards (46.9 ± 12.3 mg/dL baseline vs 47.4 ± 10 mg/dL at 1 month vs 49.8 ± 9.3 mg/dL at 3 months vs 55.4 ± 10.2 mg/dL at 1 year; p < 0.05 for all for HDL-cholesterol and 6.4 ± 2 mg/dL baseline vs 6 ± 1.7 mg/dL at 1 month vs 5.2 ± 1.3 mg/dL at 3 months vs 4.8 ± 1 mg/dL at 1 year; p < 0.05 for all for uric acid). The prevalence of metabolic syndrome decreased from 66.7% baseline to 8.3% at 5 years postoperatively (p < 0.01). Conclusions LSG was effective in terms of %EBMIL and metabolic traits improvement for Romanian patients.